Combination Treatment of C16 Peptide and Angiopoietin-1 Alleviates Neuromyelitis Optica in an Experimental Model - Yuanyuan Zhang; Kewei Tian; Hong Jiang; Beibei Wang; Shu Han (Mediators of Inflammation)
Neuromyelitis optica (NMO) is an autoimmune inflammatory demyelinating disease that mainly affects the spinal cord and optic nerve, causing blindness and paralysis in some individuals. Moreover, NMO may cause secondary complement-dependent cytotoxicity (CDC), leading to oligodendrocyte and neuronal damage. In this study, a rodent NMO model, showing typical NMO pathogenesis, was induced with NMO-IgG from patient serum and human complement. We then tested whether the combination of C16, an αvβ3 integrin-binding peptide, and angiopoietin-1 (Ang1), a member of the endothelial growth factor family, could alleviate NMO in the model. Our results demonstrated that this combination therapy significantly decreased disease severity, inflammatory cell infiltration, secondary demyelination, and axonal loss, thus reducing neural death. In conclusion, our study suggests a possible treatment that can relieve progressive blindness and paralysis in an animal model of NMO through improvement of the inflammatory milieu.